2016
DOI: 10.1080/09535314.2016.1238817
|View full text |Cite
|
Sign up to set email alerts
|

A network approach for assembling and linking input–output models

Abstract: Input-output (IO) models, describing trade between different sectors and regions, are widely used to study the environmental repercussions of human activities. A frequent challenge in assembling an IO model or linking several such models is the absence of flow data with the same level of detail for all components. Such problems can be addressed using proportional allocation, which is a form of algebraic transformations. In this paper, we propose a novel approach whereby the IO system is viewed as a network, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 43 publications
2
20
0
1
Order By: Relevance
“…[]; Rodrigues et al. []). In this procedure, re‐exports are set to zero in the multiregional MSUT, and import shares calculated from Bi,r,sdom,0 are multiplied by the import use matrix in order to give the multiregional import‐use tables.…”
Section: Compilationmentioning
confidence: 99%
See 1 more Smart Citation
“…[]; Rodrigues et al. []). In this procedure, re‐exports are set to zero in the multiregional MSUT, and import shares calculated from Bi,r,sdom,0 are multiplied by the import use matrix in order to give the multiregional import‐use tables.…”
Section: Compilationmentioning
confidence: 99%
“…pricing). The single-region import table can then be disaggregated to point of origin assuming that each industry and final consumer purchase the same relative portion of goods from exporting countries (known as the "proportionality assumption" cf Peters et al [2011]; Rodrigues et al [2016]). In this procedure, re-exports are set to zero in the multiregional MSUT, and import shares calculated from B d om,0 i,r,s are multiplied by the import use matrix in order to give the multiregional import-use tables.…”
Section: Monetary Time Seriesmentioning
confidence: 99%
“…8 Recent comparisons of physical trade matrices with high sectoral and spatial resolutions but truncated system boundaries, and multiregional input-output models with lower resolutions but complete system boundaries have shown that the two approaches lead to different and possibly even opposing results. 50,51 Approaches to link databases of different resolutions, classifications, and units have been developed, 52,53 and can be used to achieve a synergy. A prominent attempt to link FAOSTAT with EXIOBASE is the FABIO model.…”
Section: Research Agendamentioning
confidence: 99%
“…Considering whether the framework of network theory can be employed to describe the interregional interindustry linkages, Rodrigues et al (2016) illustrate the case of an input-output model in which the network approach can result in much clearer and more flexible modelling techniques than conventional matrix formulations. Additionally, they point out the advantages of the topological transformations applied to these network structures.…”
Section: Problem Definitionmentioning
confidence: 99%